Governmental systems and economic volatility in democracies - Weifeng Zhong; Chen Cheng; Christopher Li (American Enterprise Institute (AEI), 2018)
The authors study how the difference between federal and unitary systems of government can contribute to variations in economic volatility across democracies.
Keywords: A; 330; Fiscal policy; federalism